Trans-Arterial Embolization of High-Flow Renal Arteriovenous Fistula (AVF) with Concomitant Renal Artery Aneurysm - Basri, Niemah; Yusoff, Bazli Md; Samsudin, Ahmad Hadif Zaidin; Mohamad, Nasibah; Nadarajan, Chandran; Abdullah, Mohd Shafie (Journal of Clinical Interventional Radiology ISVIR, 2022)
Arteriovenous fistula (AVF) is an abnormal direct communication between an artery and the venous drainage without a capillary component. Although renal AVF is rare, detecting the disease is important to assist in management and, thus, help reverse the sequelae of the disease such as hypertension and heart failure. The clinical presentation and radiological features are important parameters that can help in the diagnosis and decision of treatment. We would like to share our successful approach to a 52-year-old female with idiopathic high-flow left renal AVF with concomitant renal artery aneurysm using a single Amplatzer vascular plug in the limit of our setting.
Keywords: renal AVF; renal artery aneurysm; Amplatzer vascular plug